2018
DOI: 10.1007/s10787-018-0450-8
|View full text |Cite
|
Sign up to set email alerts
|

Ginger rhizome enhances the anti-inflammatory and anti-nociceptive effects of paracetamol in an experimental mouse model of fibromyalgia

Abstract: GR consumption improved mechanical and thermal allodynia and mechanical hyperalgesia and improved behavioural changes related to cognitive disturbances, anxiety, and depression. In addition, GR also significantly decreased the inflammatory response of proinflammatory mediators such as NO, PGE, TXB, and IL-1β in LPS-stimulated macrophages. The effects of APAP were significantly enhanced by co-administration with GR. These findings provide evidence that the daily consumption of GR enhances the anti-nociceptive e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…57e59 In an experimental mouse model of FM, ginger improved numerous FM-related symptoms, including allodynia, hyperalgesia, cognitive disturbances, anxiety, and depression. 53 Garlic also has anti-inflammatory and analgesic properties and has been widely used since the Middle Ages. A recent review described numerous potential medical uses for garlic that ranged from acute inflammatory conditions (arthritis and hepatic injury) to migraines and vascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…57e59 In an experimental mouse model of FM, ginger improved numerous FM-related symptoms, including allodynia, hyperalgesia, cognitive disturbances, anxiety, and depression. 53 Garlic also has anti-inflammatory and analgesic properties and has been widely used since the Middle Ages. A recent review described numerous potential medical uses for garlic that ranged from acute inflammatory conditions (arthritis and hepatic injury) to migraines and vascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…An animal study into ginger-drug interactions have found that combining acetaminophen with dried powdered ginger rhizome significantly enhanced acetaminophen's anti-nociceptive effect and improved cognitive disturbances associated with chronic pain [44]. Another study noted that ginger root extract injected in rats before a sub-effective dose of morphine elicited a significant anti-nociceptive effect, higher than in groups treated with either morphine or the extract alone [45].…”
Section: Gingermentioning
confidence: 99%
“…Dried powdered ginger enhanced the effectiveness of paracetamol in vivo, without an increase in adverse events (Montserrat-de la Paz et al, 2018). Ginger oil (0.5 g/kg and 1 g/kg) exhibited protective actions against aspirin-induced gastric ulcers in rats (Khushtar et al, 2009), which was further supported by Wang et al (2011) and Khalil (2015), reporting that ginger showed protective effects against aspirin-induced ulcer formation in rats (200 mg/kg ginger powder).…”
Section: Gingermentioning
confidence: 99%